2019
DOI: 10.1007/s00259-019-04417-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting B-cell malignancies with the beta-emitting anti-CD37 radioimmunoconjugate 177Lu-NNV003

Abstract: Purpose The aim of this study was to explore the β-emitting lutetium-177 labelled anti-CD37 antibody NNV003 ( 177 Lu-NNV003, Humalutin®) for the treatment of non-Hodgkin’s lymphoma in in vitro studies and in animal models. Methods Cytotoxicity of 177 Lu-NNV003 was measured in REC-1 (mantle cell lymphoma) and DOHH-2 (diffuse large B cell lymphoma) cell lines. Biodistribution was studied in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…injected with MEC-2 cells were often euthanised due to weight loss after massive infiltration in several critical organs, while mice injected with Daudi cells were euthanised due to hind leg paralysis caused by localised infiltration of the bone marrow. Moreover, CB17 SCID mice have functional natural killer cells, whereas R2G2 do not, and the chimeric antibody NNV003 could induce some immunotherapeutic effect in this strain [8]. Accordingly, in a separate therapy study with Daudi-bearing CB17 SCID ( S4 Fig) we observed that 5 μg NNV003 had a similar anti-tumour effect as 185 kBq 212 Pb-NNV003, while 100 μg NNV003 had no effect in the MEC-2 model.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…injected with MEC-2 cells were often euthanised due to weight loss after massive infiltration in several critical organs, while mice injected with Daudi cells were euthanised due to hind leg paralysis caused by localised infiltration of the bone marrow. Moreover, CB17 SCID mice have functional natural killer cells, whereas R2G2 do not, and the chimeric antibody NNV003 could induce some immunotherapeutic effect in this strain [8]. Accordingly, in a separate therapy study with Daudi-bearing CB17 SCID ( S4 Fig) we observed that 5 μg NNV003 had a similar anti-tumour effect as 185 kBq 212 Pb-NNV003, while 100 μg NNV003 had no effect in the MEC-2 model.…”
Section: Discussionmentioning
confidence: 76%
“…This suboptimal binding was due to radiation induced oxidation of the antibody after labelling and not the conjugation method. The addition of ascorbic acid during labelling restored the binding of 212 Pb-NNV003 to the cells to approximately 80%, which is normally obtained with NNV003 labelled with lutetium-177 [8].…”
Section: Immunoreactivity Of 212 Pb-nnv003mentioning
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, our results indicate that Ramos and DOHH2 cells exposed to 177 Lu-lilotomab generate DAMPs that can further stimulate the immune system. In a clinical setting, the immunological response could be enhanced by using the chimeric version of lilotomab that can activate ADCC [47].…”
Section: Discussionmentioning
confidence: 99%